Polycyclic Aromatic Hydrocarbons from Particulate Matter 2.5 (PM2.5) in Polluted Air Changes miRNA Profile Related to Cardiovascular Disease - He, Xiaonan (Med Sci Monit, 2018)
BACKGROUND: Particulate matter 2.5 (PM2.5) in air pollution is regarded as a risk factor for cardiovascular disease (CVDs). Recently, it has become well accepted that polycyclic aromatic hydrocarbons (PAHs) in PM2.5 impacts human CVDs. However, few studies have shown miRNAs affected by PAHs play a critical role in transcriptional regulation related to cardiovascular development and disease. MATERIAL/METHODS: Human umbilical cord vein cells (HUVECs) incubated prior to treatment with PAHs at various concentrations (0, 100, 200, 300, 400, and 500 μg/ml) of PAHs particle solutions were added to the culture medium for 24 h. We performed isolation and sequencing of small RNAs and analysis of small RNA sequences and differential expression. The M3RNA database was used to predict miRNA-miRNA interactions. Tools from the DAVID database were used to perform the GO functional analysis of predicted miRNA target genes. A First-Strand cDNA Synthesis Kit was used to synthesis cDNA. RESULTS: miRNA155 was revealed as a key regulator in PAHs treatment. The putative targets of upregulated miRNA in PAHs treatment indicated that the downregulated genes were enriched in biological pathways such as Wnt signaling and ErbB signaling, which are crucial for the development of vasculature. CONCLUSIONS: In general, our results suggest that PAHs taken by PM2.5 can decrease cardiovascular-related gene expression through upregulating miRNA, which may be a new target for therapy in the future.